Waarop is sy voetstukke ingesink? - 'n Besinning oor die skepping en die big bang - Bezuidenhout, L. C. (Verbum et ecclesia, 1998)
Through the ages the debate between theology and the natural sciencesconcerning the origin of the universe was turbulent. Today the big bangtheory is almost generally accepted in scientific circles. In this article thedebate between theology and science is evaluated critically. The theologicalimplications of the big bang theory is discussed and the relevance of thecosmogony in Genesis 1 for a modem society is evaluated. Biblical modelsand scientific models of the birth of the cosmos do not have to be in conflictwith each other.